2015
DOI: 10.1098/rspb.2015.1656
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen evolution under host avoidance plasticity

Abstract: Host resistance consists of defences that limit pathogen burden, and can be classified as either adaptations targeting recovery from infection or those focused upon infection avoidance. Conventional theory treats avoidance as a fixed strategy which does not vary from one interaction to the next. However, there is increasing empirical evidence that many avoidance strategies are triggered by external stimuli, and thus should be treated as phenotypically plastic responses. Here, we consider the implications of av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…On the other hand, Arabidopsis could not optimize at the same time tolerances to viruses displaying different virulence levels (negative association between these tolerances), with LS-CMV and JPN1-TuMV (lower virulence) inducing different and mutually exclusive life-history modifications than UK1-TuMV (higher virulence). A number of experimental works reported that pathogen-driven changes in host life-history traits can be either genetically determined or the consequence of phenotypic plasticity ( Michalakis & Hochberg, 1994; Schlichting & Pigliucci, 1998; McLeod & Day, 2015 ). Thus, it could be hypothesized that one or both of these two types of determinisms may be involved in the observed tolerance-tolerance trade-offs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Arabidopsis could not optimize at the same time tolerances to viruses displaying different virulence levels (negative association between these tolerances), with LS-CMV and JPN1-TuMV (lower virulence) inducing different and mutually exclusive life-history modifications than UK1-TuMV (higher virulence). A number of experimental works reported that pathogen-driven changes in host life-history traits can be either genetically determined or the consequence of phenotypic plasticity ( Michalakis & Hochberg, 1994; Schlichting & Pigliucci, 1998; McLeod & Day, 2015 ). Thus, it could be hypothesized that one or both of these two types of determinisms may be involved in the observed tolerance-tolerance trade-offs.…”
Section: Discussionmentioning
confidence: 99%
“…We wish to use (3) to understand how selection, stochasticity, and epidemiology interact to shape the evolution of sterility virulence. To do so, we adopt the approach we used elsewhere (McLeod and Day 2019), and ask what is the likelihood of observing the stochastic process in a particular state? If we are more likely to observe the process in a state in which strain i is most frequent, then we will say strain i is favored.…”
Section: Resultsmentioning
confidence: 99%
“…Instead these previous studies have focused upon how spatial structure (O'Keefe and Antonovics ; Lion and Gandon ) or host coevolution (Best et al. ; Ashby and Boots ; McLeod and Day ) can limit the evolution of sterility virulence, without considering why sterility virulence is more common for STIs than directly transmitted pathogens.…”
mentioning
confidence: 99%
See 2 more Smart Citations